PENGARUH POSISI TALI UTAMA DAN KECEPATAN ARUS TERHADAP GERAKAN SWINGING DAN DIVING DARI MODEL TROLLING BOARD - Budiman, Johnny; Mathias, Yan A; Katiandagho, Elof M; Kalangi, Patrice NI; Telleng, Aglius RT; Reppie, Emil; Kumajas, Henry J (Sam Ratulangi University, 2011)
Trolling board is an important troll line accessory which can produce swinging and diving movements of the lure. A laboratory study on the effect of trolling board main line position and current speed on swinging and diving movements was done in a water circulating tank at the Faculty of Fisheries and Marine Science, Sam Ratulangi University. At low speed, the widest swing reached at main line position near the center of trolling board, but at high speed, it reached main line position near the fore tip. Swinging frequency decreased with the current speed. The depth of diving increased as the main line position got closer to the tip and increased with current speed.